Cluster randomised controlled trial of an m-health intervention in centre-based childcare services to reduce the packing of discretionary foods in children's lunchboxes: study protocol for the 'SWAP IT Childcare' trial. Issue 5 (1st June 2019) - Pond, Nicole; Finch, Meghan; Sutherland, Rachel; Wolfenden, Luke; Nathan, Nicole; Kingsland, Melanie; Grady, Alice; Gillham, Karen; Herrmann, Vanessa; Yoong, Sze Lin
Abstract : Introduction: In many developed nations, including Australia, a substantial number of children aged under 5 years attend centre-based childcare services that require parents to pack food in lunchboxes. These lunchboxes often contain excessive amounts of unhealthy ('discretionary') foods. This study aims to assess the impact of a mobile health (m-health) intervention on reducing the packing of discretionary foods in children's childcare lunchboxes. Methods and analysis: A cluster randomised controlled trial will be undertaken with parents from 18 centre-based childcare services in the Hunter New England region of New South Wales, Australia. Services will be randomised to receive either a 4-month m-health intervention called 'SWAP IT Childcare' or usual care. The development of the intervention was informed by the Behaviour Change Wheel model and will consist primarily of the provision of targeted information, lunchbox food guidelines and website links addressing parent barriers to packing healthy lunchboxes delivered through push notifications via an existing app used by childcare services to communicate with parents and carers. The primary outcomes of the trial will be energy (kilojoules) from discretionary foods packed in lunchboxes and the total energy (kilojoules), saturated fat (grams), total and added sugars (grams) and sodium (milligrams) from all foods packed in lunchboxes. Outcomes will be assessed by weighing and photographing all lunchbox food items at baseline and at the end of the intervention. Ethics and dissemination: The study was approved by the Hunter New England Local Health District Human Ethics Committee (06/07/26/4.04) and ratified by the University of Newcastle, Human Research Ethics Committee (H-2008–0343). Evaluation and process data collected as part of the study will be disseminated in peer-reviewed publications and local, national and international presentations and will form part of PhD student theses. Trial registration number: ACTRN12618000133235; Pre-results.